Study on the carrier transport mechanism in single-crystalline Br-doped SnSe2. (November 2020) - Bang, Geukchan; Ryu, Jung Hyun; Lee, Kimoon
Abstract: We investigate the carrier transport mechanism in Br-doped SnSe2 single crystals by characterizing electrical properties in the high-temperature ( T ) region (300–500 K). In-plane electrical resistivity decreases with the introduction of Br dopant in layered SnSe2 single crystals owing to the increase of the electron carrier concentration ( n e ), indicating Br is an efficient electron donor for SnSe2 . From the T dependence of n e, the thermally activated behavior disappears when n e exceeds approximately 10 18  cm −3, suggesting degenerate conduction easily occurs by electron doping from 300 to 500 K. The Hall carrier mobility ( μ H ) depends on T according to the relation μ H  ~  T − γ, and γ is significantly reduced from 1.68 to 0.52 by Br doping. This strongly evidences that the homopolar optical mode phonon, as the main scatterer for carrier transport at high T, is effectively quenched through the carrier doping. Highlights: Single-crystalline layered SnSe2 samples doped with various Br contents were grown by the melt-solidification method. The carrier transport mechanism in Br-doped SnSe2 single crystals was investigated by characterizing electrical properties at various temperatures. It is clarified that Br is one of the most effective donors for layered SnSe2 that can effectively suppress the homopolar optical mode phonon.